Analisis Kinerja Keuangan pada PT Aneka Tambang (Persero) Tbk yang Tercatat di BEI pada Tahun 2022-2023 - M. Fiqri Faisal; Desy Suryani (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2024)
Financial reports are an important medium in the economic decision making process. Companies must prepare financial reports that describe all transactions in the company. By analyzing financial reports, management can determine the right steps so that company goals can be achieved. In analyzing the company's financial performance based on the calculation of financial ratios at PT. Aneka Tambang Tbk required data is a financial report consisting of financial position (balance sheet) and profit and loss statement. The company's Current Ratio was recorded at 195.83%, which indicates that the company has high enough liquidity to meet its short-term obligations. However, in the following year, namely 2023, the Current Ratio will increase to 233.94%. The company's Debt to Equity ratio was recorded at 41.85%, the company's NPM was recorded at 8.31%, which indicates that the company succeeded in converting around 8.31% of its total revenue into net profit. However, in the following year, namely 2023, NPM will decrease to 7.49%. Receivable Turnover (RTO) financial ratio analysis provides an understanding of PT Aneka Tambang Tbk's efficiency in managing its receivables from 2022 to 2023. In 2022, the company's RTO was recorded at 881.5%..